An analysis of NESTROFT and Red cell indices in evaluating antenatal mothers for Beta Thalassemia trait - Safia, Rana; Jairajpuri, Zeeba S; Khetrapal, Shaan; Hassan, MJ; Gupta, Monika; Jetley, Sujata (Bangladesh Journal of Medical Science, 2018)
Background: The frequency of thalassemia trait is about 3% worldwide, while in developing countries like India, it is a major cause of burden on the health care system. Naked eye single tube red cell osmotic fragility test (NESTROFT) used in population screening for beta thalassemia trait. It is a simple, low cost, reliable and most suitable screening test for β BTT, with a sensitivity of 99.8% in regions with high prevalence rates. Material &Methods: The present study was conducted in the Department of Pathology and included a total of 174 antenatal cases, attending the Out Patient Department of Obstetrics and Gynecology of a tertiary health care center in New Delhi between June 2011 to January 2012. The aim of the study was to screen mothers antenatally for early detection of BTT and to test the validity of NESTROFT in detection of thalassemic carriers of this area. Results: 174 pregnant women attending antenatal clinics were screened for detecting hemoglobinopathy with the help of NESTROFT, red cell indices, haemoglobin electrophoresis and HPLC It was seen that only four cases were BTT while ten were of microcytic anaemia and two had normal red cell indices. Conclusion: antenatal diagnosis of BTT is an important screening programme to reduce the burden of birth of children suffering from thalassemia and other hemoglobinopathies. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.411-416